“WHEN IN THE ‘BROTHER’ THE STRANGER IS ACKNOWLEDGED”: From Identity to Alterity and Dialogue, According to Emmanuel Levinas - Burggraeve, Roger (Journal of Dharma, 2018)
A crucial question in a pluralist society is how justice can be done to alterity without endangering thereby one’s identity. Levinas’ dialogical phenomenology of the same and the other, and of responsibility, sets us on the track of ‘fraternity’ as human condition. As ethical condition of ‘solidarity’ this fraternity transcends sex and gender, even if the concept is originally rooted in biology. Inspired by Levinas, it is explained how fraternity attains its full sense when, in the brother, the stranger is acknowledged (and not the opposite: ‘when in the stranger the brother is recognized’). This ‘ethical fraternity’ makes it possible to realize equality in society, and to promote a respectful and authentic inter-religious, or rather ‘interconvictional’ dialogue. Such an open dialogue appeals to an asymmetric and reciprocal mastership and critical learning from each other.